Does echocardiography accurately reflect CMR-determined changes in left ventricular parameters following exercise training? A prospective longitudinal study - Spence, Angela; Naylor, L.; Carter, H.; Dembo, L.; Murray, C.; O'Driscoll, G.; George, K.; Green, D. (The American Physiological Society, 2013)
Cardiac adaptation in response to exercise has historically been described using echocardiography. Cardiac magnetic resonance (CMR), however, has evolved as a preferred imaging methodology for cardiac morphological assessment. While direct imaging modality comparisons in athletes suggest that large absolute differences in cardiac dimensions exist, it is currently unknown whether changes in cardiac morphology in response to exercise training are comparable when using echocardiography and CMR. Twenty-two young men were randomly assigned to undertake a supervised and intensive endurance or resistance exercise-training program for 24 wk. Echocardiography and CMR assessment of left ventricular (LV) mass, LV end-diastolic volume, internal cavity dimensions, and wall thicknesses were completed before and after training. At baseline, pooled data for all cardiac parameters were significantly different between imaging methods, while LV mass (r = 0.756, P < 0.001) and volumes (LV end-diastolic volume, r = 0.792, P < 0.001) were highly correlated across modalities. Changes in cardiac morphology data with exercise training were not significantly related when echocardiographic and CMR measures were compared. For example, posterior wall thickness increased by 8.3% (P < 0.05) when assessed using echocardiography, but decreased by 2% when using CMR. In summary, echocardiography and CMR imaging modalities produce findings that differ with respect to changes in cardiac size and volume following exercise training.